Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1111/and.13750
|View full text |Cite|
|
Sign up to set email alerts
|

IL‐17F facilitates prostate cancer cell malignant phenotypes via activation of the PI3K/AKT signalling pathway

Abstract: Prostate cancer (PCa) is known as one of the most common cancers in men all over the world. Previous studies have identified that the pro-inflammatory mediator interleukin-17F (IL-17F) aggravates the progression of several diseases. However, whether IL-17F plays a role in PCa is still lack of enough exploration. In this study, IL-17F expression was strikingly upregulated in PCa tissues. Treatment of IL-17F promoted cell viability at a dose-dependent manner. Further, functional assays were implemented by treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The previous study demonstrated that increased expression of thrombomodulin might reduce the migration of cancer cells by restraining PI3K and Akt [ 20 ]. Furthermore,increasing evidence showed that the anticoagulant drugs, such as warfarin and heparin, have antitumor effects both in vivo and in vitro [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The previous study demonstrated that increased expression of thrombomodulin might reduce the migration of cancer cells by restraining PI3K and Akt [ 20 ]. Furthermore,increasing evidence showed that the anticoagulant drugs, such as warfarin and heparin, have antitumor effects both in vivo and in vitro [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Taxifolin inhibits androgen production in Leydig cells, inhibits PCa cell growth, and induces PCa cell apoptosis [ 16 ]. Quercetin blocks AR activity and inhibits PCa development [ 42 ]. Kaempferol significantly inhibits dihydrotestosterone (DHT) AR activation, while reducing downstream targets of AR and ultimately inhibiting PCa cell proliferation, angiogenesis, and invasion [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…In cancerous prostate samples, IL-17, IL-6, and IL-8 were strongly correlated [ 124 ]. Moreover, a recent study found that IL-17F activated the PI3K/Akt signaling pathway to enhance PCa cell malignant phenotypes, indicating a potential treatment target for PCa [ 125 ]. A Galician single nucleotide polymorphism (SNP) analysis found that the IL-17 gene polymorphism −197G > A increases PCa risk [ 126 ].…”
Section: Proinflammatory Cytokines and CXC Chemokinesmentioning
confidence: 99%